2014
DOI: 10.1159/000356498
|View full text |Cite
|
Sign up to set email alerts
|

Inverse and Direct Cancer Comorbidity in People with Central Nervous System Disorders: A Meta-Analysis of Cancer Incidence in 577,013 Participants of 50 Observational Studies

Abstract: Background: There is a lack of scientific consensus about cancer comorbidity in people with central nervous system (CNS) disorders. This study assesses the co-occurrence of cancers in patients with CNS disorders, including Alzheimer's disease (AD), amyotrophic lateral sclerosis (ALS), autism spectrum disorders, Down's syndrome (DS), Huntington's disease (HD), multiple sclerosis (MS), Parkinson's disease (PD) and schizophrenia (SCZ). Method: Comprehensive search in PubMed/MEDLINE, Scopus and ISI Web of Knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
151
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(168 citation statements)
references
References 158 publications
10
151
2
5
Order By: Relevance
“…In a study [110], about 50% of psychiatric patients who suffered from medical conditions remained undiagnosed as to the underlying physical disorders; primary care physicians failed to diagnose the physical illness in 32% of cases and psychiatrists in 48%, even though having a psychiatric disorder may be associated with an increased risk of medical illness (e.g. breast cancer) [111]. Primary care physicians may not pursue a medical workup of cases that appear to be overtly psychiatric in nature; similarly, patients having had previous psychiatric treatment may prejudice the clinical judgment of the physician [112].…”
Section: Discussionmentioning
confidence: 99%
“…In a study [110], about 50% of psychiatric patients who suffered from medical conditions remained undiagnosed as to the underlying physical disorders; primary care physicians failed to diagnose the physical illness in 32% of cases and psychiatrists in 48%, even though having a psychiatric disorder may be associated with an increased risk of medical illness (e.g. breast cancer) [111]. Primary care physicians may not pursue a medical workup of cases that appear to be overtly psychiatric in nature; similarly, patients having had previous psychiatric treatment may prejudice the clinical judgment of the physician [112].…”
Section: Discussionmentioning
confidence: 99%
“…In interpreting our findings, several factors, particularly epidemiology of melanoma, natalizumab‐associated progressive multifocal leukoencephalopathy (PML), various aspects of the TOUCH Risk Management (RiskMAP) Action Plan, and the Safety Surveillance Program in this RiskMAP (Table 3), potential pathophysiology, and an overview of pharmacovigilance efforts for opportunistic complications of medications, should be considered 6, 7, 8, 9, 10, 11, 13, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies evaluated incidence of melanoma among MS patients, although none reported convincing epidemiologic or biologic associations or relative risk estimates 26, 27, 28, 37. Capkun et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the existence of inverse comorbidity with cancer was confirmed for PD and HD. [99,100] It is possible that common mechanism/s may be involved in the pathogenesis of LONDD and cancer. These mechanisms are probably subject to modulation by other genetic and/or environmental factors so that the potential outcomes would rarely coincide in the same patient.…”
Section: Cancer and Londd: Extremes Of A Wide Spectrum?mentioning
confidence: 99%